2009
DOI: 10.2308/accr.2009.84.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Tax Reporting Aggressiveness and Its Relation to Aggressive Financial Reporting

Abstract: We investigate the association between aggressive tax and financial reporting and find a strong, positive relation. Our results suggest that insufficient costs exist to offset financial and tax reporting incentives, such that nonconformity between financial accounting standards and tax law allows firms to manage book income upward and taxable income downward in the same reporting period. To examine the relation between these aggressive reporting behaviors, we develop a measure of tax reporting aggressiveness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
900
18
172

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,158 publications
(1,246 citation statements)
references
References 35 publications
47
900
18
172
Order By: Relevance
“…Some examples of these studies are Gupta and Newberry (1997), Rego (2003), Graham and Tucker (2006), Frank et al (2009), andWilson (2009).…”
Section: Aspects Related To Tax Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples of these studies are Gupta and Newberry (1997), Rego (2003), Graham and Tucker (2006), Frank et al (2009), andWilson (2009).…”
Section: Aspects Related To Tax Managementmentioning
confidence: 99%
“…In this vein, Desai and Dharmapala (2006) report that tax management is a legal transfer of State resources to companies with a view to increase their performance, by reducing expenses on taxes. As a result, many researchers have shown that tax management is a valuable activity for shareholders (Bankman, 1999;Graham & Tucker, 2006;Desai & Dharmapala, 2007;Frank et al, 2009;Wilson, 2009).…”
Section: Aspects Related To Tax Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The BTDs have been proposed as a measure of both earnings management and corporate tax avoidance (Graham, Raedy & Shackelford 2012). Corporations that are relatively successful at tax avoidance are likely, although not necessarily able, to sustain large differences between accounting income and taxable income (Alexander, Ettredge, Stone & Sun 2008;Dyreng et al 2008;Frank et al 2009;Rego & Wilson, 2009). Wilson (2009) found that BTDs are larger for corporations accused of engaging in tax shelters than for a matched sample of non-accused corporations.…”
Section: Identifying Corporate Tax Avoidancementioning
confidence: 99%
“…These key words are searched for each firm-specific observation, and the observation period ranges from 1 January 2010 to 31 December 2013. This is to capture the initial trend of the amount of news coverage of tax aggressiveness which is broadly defined as downward management of taxable income through tax planning activities (Frank et al, 2009) that do not necessarily break the law. 8 Consistent with prior literature (Chen et al, 10 2010), I use the terms "tax aggressiveness" and "tax avoidance" interchangeably throughout this paper.…”
Section: Sample and Datamentioning
confidence: 99%